Integration, social distress, and policy formation - Oded Stark (University of Bonn, Center for Development Research (ZEF), 2012)
I study the integration of regions in the form of a merger of populations, which I interpret as a revision of people's social space and their comparison set; I illustrate the way in which a merger can aggravate social distress; and I consider policy responses. Specifically, I view the merger of populations as a merger of income vectors; I measure social distress by aggregate relative deprivation; I demonstrate that a merger increases aggregate relative deprivation; and I show that a social planner is able to reverse this increase by means of least-cost, post-merger increases in individual incomes, but is unable to counter it by relying exclusively on a self-contained income redistribution that retains individual levels of wellbeing at their pre-merger levels.
Keywords: D04; D63; F55; H53; P51; 330; Integration of regions; Merger of populations; Revision of social space; Aggregate relative deprivation; Social distress; Policy responses; Politische Integration; Bevölkerung; Soziale Integration; Einkommensverteilung; Sozialer Konflikt; Konsuminterdependenz; Einkommenspolitik; Theorie